Independent non-legal advocacy in the child protection context: A descriptive review of the literature - Fitt, Kate (2023)
Objective: To review the current literature on the use and value of independent non-legal advocacy for parents in the context of child protection. Method: A descriptive literature review was undertaken to identify, review, synthesize and unify the available literature on independent non-legal advocacy for parents in a child protection context. A systematic search resulted in 45 publications published between 2008 and 2021 being included in the review. Each publication was then thematically analyzed. Outcome: The role and context of different forms of independent non-legal advocacy are described. This is followed by an overview of the three overarching themes identified through thematic analysis - human rights, improving parenting and child protection practice and eco nomic benefits. Conclusions: The topic of independent non-legal advocacy in child protection settings is an important, under-researched topic. The increasing number of positive outcomes noted in small scale program evaluations suggests the role of independent non-legal advocate may hold signif icant benefits for families, service systems and governments. Implications for service delivery include enhanced social justice and human rights for parents and children.